Obstetric factors and pregnancy outcome in placenta previa - Ojha, N (Journal of Institute of Medicine Nepal, 2013)
Introduction: Placenta previa is one of the major causes for maternal morbidity and mortality. The aim of this study was to analyze the obstetrical factors associated with placenta previa and to find out the maternal and perinatal outcome of these cases. Methods: This was a retrospective study conducted in the Department of Obstetrics and Gynecology of TUTH. Hospital chart records of four years (1st January 2008 to 31st December 2011) were collected. Chart records of all women who had undergone cesarean section for placenta previa were reviewed. Relevant clinical findings were noted. Results: During the study period, there were 82 cases of cesarean sections done for placenta previa, which is 0.55% of the total deliveries. Of the eighty two cases, charts could be obtained of the 70 patients for the analysis. 21.4% had total placenta previa. Maximum women were in age group 26-30 years. Sixty one percent of the patients were multipara. Sixteen patients had history of cesarean section and 20 cases had abortions in previous pregnancy. Malpresentation was present in more than one fifth (21.4%) of the patient. 45.7% of the babies were preterm and 27% were low birth weight babies. Seven babies had neonatal death. Almost one third (31.4%) of the patient had blood loss ≥500ml. There were four cases with blood loss ≥1000ml. Among them two had loss of more than two liters. Ten patients required blood transfusion. One patient had cesarean hysterectomy. Conclusion: Placenta previa poses danger to both the mother and the baby. There is high maternal morbidity and adverse perinatal outcome. DOI: http://dx.doi.org/10.3126/joim.v34i2.9053 Journal of Institute of Medicine August, 2012; 34:2 38-41